Angular analyses of b → sll transitions at CMS. (January 2019) - Li, Linwei
Abstract: The flavour changing neutral current decays are interesting probes for searching for new physics. Angular distributions of b → sℓ + ℓ − transition processes of both B 0 → K *0 µ + µ − and B + → K + µ + µ − are studied using a sample of proton-proton collisions at s = 8 TeV collected with the CMS detector at the LHC, corresponding to an integrated luminosity of 20.5 fb −1 . Angular analyses are performed to determine P 1 and P ′ 5 angular parameters for B 0 → K *0 µ + µ − and AFB and FH parameters for B + → K + µ + µ −, all as functions of the dimuon invariant mass squared. All of the measurements are consistent with the standard model predictions.